Cost-Efficiency Analysis of the Improved Web-Based Planning, Budgeting, and Reporting System (PlanRep) in Tanzania - Ruhago, George M.; Kapologwe, Ntuli A.; Ngalesoni, Frida N.; Kengia, James T.; Kibusi, Stephen M.; Kalolo, Albino; Kitali, Erick J.; Mtatifikolo, James D.; Masuha, Sutte R.; Kikula, Amani; Mtei, Gemini (Frontiers in Health Services, 2022)
Background: Information systems offer unlimited potential for innovation and digitalization of management functions to facilitate citizen participation and improve accountability, transparency and efficiency in government operations and service delivery. In line with this, for more than one decade, Tanzania implemented integrated planning, budgeting and reporting system (PlanRep) that was used to prepare plans and budgets at the local government authorities (LGAs) using a desktop application. In 2017 PlanRep was upgraded to a web-based system to address several challenges, including poor coordination and high cost involved in preparing plans and budgets. However, operational evidence regarding the cost-efficiencies and benefits of shifting to web-based PlanRep has not been explored. This study aims at addressing this gap by assessing efficiency gains in terms of cost and time. Methods: The study applied a retrospective before and after study design whereby quantitative data on how much time and the cost was incurred by LGAs when preparing their budget one year before the introduction of PlanRep and one year after. Parallelly, qualitative data were collected through key informant interviews with selected LGAs officials, Regional Secretariats (RSs), PORALG, and system end-users such as heads of health facilities and schools. Secondary data was analyzed by comparing time and cost used before and after Web-based PlanRep, while thematic analysis was employed for qualitative data. Results: Analysis showed a 53% reduction (from USD 3.8 million in 2017/18 to USD 1.8 million in 2018/19) in the total costs LGAs incurred during planning and budgeting after introducing the web-based PlanRep. The main efficiency gain was related to per diem costs. The analysis also showed significant time saving from an average of 87 days in 2017/18 to only eight (8) days in 2018/19. PlanRep system end users also acknowledged that the introduction of web-based PlanRep has significantly saved their time and costs in preparation of plans and budget. Conclusion: Introduction of the web-based planning, budgeting and reporting systems has resulted in tremendous cost reduction, time savings, transparency, accountability and workload reduction., Findings offer operational evidence to guide the implementation and scale up of similar systems in countries that share equivalent circumstances like Tanzania.